Mapping the Landscape of Customer Loyalty Research in Budget Hospitality :Bibliometric Insights from Two-Star Hotel Studies - Ayuanti, Rafikhein Novia; Sudarmiatin; Wardoyo, Cipto; Mukhlis, Imam; Biahmada, AM Maqdum; Munir, Miftahul (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2026)
This study provides a bibliometric review of customer loyalty research within the hospitality industry, with particular emphasis on two-star hotel settings. Using data retrieved from the Scopus database from 2020 to 2025, a total of 73 articles were analyzed through Biblioshiny and VOSviewer to map publication trends, influential authors, core journals, contributing countries, and thematic structures. The analysis reveals that customer satisfaction, corporate social responsibility (CSR), service quality, and corporate image constitute the most dominant themes in hospitality loyalty studies. Despite this progress, research explicitly addressing loyalty development in two-star hotels remains limited, indicating a significant gap related to sustainable loyalty practices in budget and mid-scale accommodations. The findings contribute to a deeper understanding of the intellectual landscape and evolution of loyalty research in hospitality. This review highlights the need for future studies to examine loyalty strategies tailored to lower-star hotels, especially those facing greater constraints in service delivery and resource capacity.